Principles of optimal mental health care for adolescents and the impact of system-wide barriers. (3rd May 2020) - Platell, Monique; Martin, Karen; Cook, Angus; Fisher, Colleen
ABSTRACT: Objective: (i) identify principles underpinning optimal mental health service provision for adolescents as identified by mental health service professionals; (ii) identify mental health service practice- and policy-level factors which act as facilitators and barriers to providing optimal care for adolescents. Method: qualitative approach utilising semi-structured, face-to-face interviews with 23 purposively recruited government and non-government mental health professionals. The data were thematically analysed. Results: The mental health professionals identified three main service feature principles underpinning optimal mental health service provision for adolescents: (1) flexibility, (2) consistency; and (3) trust. Participants identified practices within mental health services that were facilitators and barriers to these three principles. Discussion: The main characteristics mental health professionals believe are required to provide optimal mental health care for adolescents, differentially contrast with the reported current service provision process. Many service practices, such as triage processes and entry criteria, were perceived to be strategies that services implement to protect themselves from the high stress and demand they face rather than for adolescent benefit. These results highlight that mental health services for adolescents remain fragmented, with little system-wide planning to stream-line processes and thus negatively impacting adolescent mental health care. Ongoing demands of the system have created an environment where constant client turnover and rigidity are a must to cope. Abstract :